Artificial Intelligence and English Classroom: The Implications of AI Toward EFL Students’ Motivation - Adolfina M. S. Moybeka; Nur Syariatin; Devilito P. Tatipang; Dina Amaliyah Mushthoza; Ni Putu Juliani Lestari Dewi; Sulfany Tineh (Edumaspul: Jurnal Pendidikan, 2023)
The integration of Artificial Intelligence (AI) into the realm of English as a Foreign Language (EFL) education has brought forth transformative possibilities, particularly in the context of student motivation. This research employs a mixed-methods approach, encompassing quantitative surveys and qualitative study of previous literature, to delve into the multifaceted dimensions of EFL students' motivation within the AI-driven learning environment. Quantitative data collection involves administering structured survey questionnaires to a diverse group of EFL students who have experienced AI-based language learning tools. Qualitative insights are gleaned through document/literature study, aiming to provide in-depth narratives and understandings concerning the participants' experiences, attitudes, and perceptions regarding AI in EFL classroom. This integration highlights the nuanced interplay between AI technologies and motivation factors, shedding light on how AI can enhance intrinsic motivation, boost self-efficacy, and facilitate personalized language learning experiences. Moreover, the study addresses ethical considerations, ensuring the privacy and well-being of participants throughout the research process. Ultimately, the research contributes to the growing body of knowledge on AI's role in education and its potential to shape the future of EFL instruction. By unveiling the implications of AI on EFL students' motivation, this study provides valuable insights for educators, policymakers, and stakeholders, guiding the effective integration of AI to foster enduring and enthusiastic language learners in an increasingly digital age.